Study on decentralized voltage for hydropower distributed geberation for IEEE 14 bus test system - Niruben Kumar Jaya Kumar (2023)
Distribution generation is increasing in popularity in distribution system as an alternative power source to help supplement power and act as a voltage control of a distribution system.